Effect of substrate temperature on gold-catalyzed silicon nanostructures growth by hot-wire chemical vapor deposition (HWCVD) - Chong, S.K.; Goh, B.T.; Aspanut, Z.; Muhamad, M.R.; Dee, C.F.; Rahman, S.A. (2011)
The effect of substrate temperature on the structural property of the silicon nanostructures deposited on gold-coated crystal silicon substrate by hot-wire chemical vapor deposition (HWCVD) was studied. The uniformity and size of the as-grown silicon nanostructures is highly influenced by the substrate temperature. XRD, Raman and HRTEM measurements show the silicon nanostructures consist of small crystallites embedded within amorphous matrix. The crystallite size of the as-grown silicon nanostructures decreases with increases in substrate temperature. FTIR shows that these silicon nanostructures are highly disordered for sample prepared at substrate temperature above 250 degrees C. The correlation of crystallinity and structure disorder of the silicon nanostructures growth at different substrate temperature was discussed. (C) 2010 Elsevier B.V. All rights reserved.